Applied quasi-cyclic LDPC codes from doubly-extended RS code and cyclic MDS code - ZHANG Guo-hua; WANG Xin-mei (Tongxin xuebao)
Based on doubly-extended RS codes and cyclic MDS codes,two construction schemes were proposed for ap-plied quasi-cyclic LDPC codes whose Tanner graph is free of 4-cycles.In the first approach,all the nonzero codewords within a doubly-extended RS code were employed,and hence provided more flexible parameters than the original or sin-gly-extended RS codes.Equivalent to the method from doubly-extended RS code,a straightforward procedure was de-rived,by which given generator polynomial of an RS code,LDPC codes could be constructed directly without pretreat-ment such as double extension and classification of codewords.In the second method,generator polynomials of cyclic MDS codes were utilized in a straightforward manner to build quasi-cyclic LDPC codes with its Tanner graph free of 4-cycles.Experimental results showed that the constructed codes from the two methods perform well over AWGN channels.